PENGEMBANGAN BAHAN PEMBELAJARAN BLENDED LEARNING DALAM MATA KULIAH - Irawan Suprapto; Dewi Sri Kuning (Universitas Muhammadiyah Kotabumi, 2021)
Learning needs to be designed based on a need assessment and the need to develop learning materials that can answer learning problems in higher education. The development of Blended Learning materials is carried out to provide learning that can accommodate the breadth of required discussion and to elaborate on students' understanding, practice, and attitudes as competencies that are expected to be achieved in course learning. This paper aims to provide information about designing and producing blended learning materials that can solve learning problems. Dick and Carey's system approach model and Allan Jolliffe's web-based materials development model were used in the development of blended learning materials. The combination of learning materials, both printed and non-printed materials, can be arranged in face-to-face or non-face-to-face learning. Learning makes student activities and learning outcomes that make maximum learning outcomes. This paper describes the development of blended learning materials in higher education.